Survey on Giant Constellation Cloud Network Integration - Dan ZHANG; Jingjing LI; Tian LIU; Sunjie TAO; Ziping LYU (天地一体化信息网络, 2023)
Thanks to the development of aerospace technology and the rise of concepts such as cloud computing and edge computing, cloud network convergence networks based on giant constellations are expected to become an important part of the integrated construction of star-ground and 6G global communication networks.Unlike terrestrial communication networks, constellation network topology is highly dynamic and time-varying, with strong resource and link heterogeneity, and other characteristics that pose challenges for cloud network convergence.The characteristics of giant constellations and the development status of terrestrial cloud network convergence was summarized, the urgent needs and challenges of cloud network convergence in giant constellations were analyzed, and the innovation of satellite internet cloud network convergence architecture, the use of resource virtualization technology, information sensing and routing path planning based on artificial intelligence algorithms, and cloud computing and edge collaborative computing were potential directions for future satellite-based cloud network convergence technology development direction were further pointed out.